A temperature-based synthesis and characterization study of aluminum-incorporated diamond-like carbon thin films - Ghadai, Ranjan Kumar; Shanmugasundar, G.; Cepova, Lenka; Das, Soham; Kumar Mahto, Premchand; Kalita, Kanak (Frontiers in Mechanical Engineering, 2023)
The present work deals with the study of various properties of Aluminum (Al) incorporated Diamondlike Carbon (DLC) thin films synthesized using Atmospheric pressure chemical vapour deposition (APCVD) technique with variation in deposition temperature (𝑇 𝑑 ) and keeping the 𝑁 2 flow rate consant. The analysis of surface morphology, resistance to corrosion, nano hardness (𝐻) and young's modulus (𝐸) of the coatings is carried out by atomic force microscopy (AFM), corrosion test, Scanning Electron Microscopy (SEM) and Nano-Indentation test.SEM results showed smoother surface morphology of the coatings grown at different process temperatures. With an increase in process temperature, the coating roughness (Ra) lies in the range of 20 to 36 µm. The corrosion resistance of the coating found to be reduced with a consecutive increase in the deposition temperature from 800℃ to 880℃. However, after 880℃ again the resistance is increased, and it may due to the presence of more Al weight percentage in the coating. The nanoindentation result revealed that the coating 𝐻 and 𝐸 increase with enhancement in CVD process temperature. The elastic-plastic property indicated by 𝐻/𝐸 and 𝐻 3 /𝐸 2 which is also an indication of wear properties of the coating are studied using the nanoindentation technique. The residual stresses (𝜎) calculated by using Stoney's equation revealed a reduction in residual stress with an increase in the process temperature.